Proteomic characterization of serum proteins from Atlantic salmon (Salmo salar L.) from an outbreak with cardiomyopathy syndrome. Issue 11 (5th July 2021) - Costa, Janina Z.; del Pozo, Jorge; McLean, Kevin; Inglis, Neil; Sourd, Philippe; Bordeianu, Andrei; Thompson, Kim D.
Abstract: Cardiomyopathy syndrome (CMS), caused by piscine myocarditis virus (PMCV), is a serious challenge to Atlantic salmon ( Salmo salar L.) aquaculture. Regrettably, husbandry techniques are the only tool to manage CMS outbreaks, and no prophylactic measures are available at present. Early diagnosis of CMS is therefore desirable, preferably with non‐lethal diagnostic methods, such as serum biomarkers. To identify candidate biomarkers for CMS, the protein content of pools of sera (4 fish/pool) from salmon with a CMS outbreak (3 pools) and from clinically healthy salmon (3 pools) was compared using liquid chromatography–electrospray ionization–tandem mass spectrometry (LC‐ESI‐MS/MS). Overall, seven proteins were uniquely identified in the sera of clinically healthy fish, while 27 proteins were unique to the sera of CMS fish. Of the latter, 24 have been associated with cardiac disease in humans. These were grouped as leakage enzymes (creatine kinase, lactate dehydrogenase, glycogen phosphorylase and carbonic anhydrase); host reaction proteins (acute‐phase response proteins—haptoglobin, fibrinogen, α2‐macroglobulin and ceruloplasmin; and complement‐related proteins); and regeneration/remodelling proteins (fibronectin, lumican and retinol). Clinical evaluation of the suitability of these proteins as biomarkers of CMS, either individually or as part of a panel, is a logical next step for the development of early diagnostic tools for CMS.